A Qur’anic discourse analysis: exploring values in Nouman Ali Khan’s Amazed by the Qur’an - Nurhamidah, Idha; Santosa, Riyadi; Djatmika, Djatmika; Yustanto, Henry (Penerbit Universiti Kebangsaan Malaysia, 2025)
This research addresses the critical need to understand the linguistic and rhetorical dimensions of religious lectures (Khutbahs) delivered by Nouman Ali Khan, exploring the Qur'anic themes. As a linguist, the uniqueness of his lecturing and interpreting always unzips the Qur'an linguistically based_ unravelling the intricacies of language and discourse. The qualitative method involves text analysis of 20 Khutbahs, examining linguistic features, textual organisation, and rhetorical strategies employed by the speaker. The study explores the rhetoric of Qur'anic discourse across various life aspects, emphasising linguistic registers and the integration of Arabic and English. The primary data comprises transcripts of 20 Khutbahs from the "Amazed by the Qur'an" channel, covering diverse topics such as ethical considerations, historical narratives, and linguistic intricacies present in the Qur'an. The khutbahs serve as a rich source of linguistic and moral insights. The findings reveal the diverse applications of linguistic registers, showcasing the Qur'an's value in addressing social, business, and personal dimensions of life. The integration of Arabic and English caters to a broad audience. The study emphasises the significance of linguistic competence and rhetorical dimensions in conveying Qur'anic messages, encompassing Halliday's Systemic Functional Linguistic (SFL) tenor, mode, field, and rhetorical strategies. This research contributes to understanding the 'no linguistical mistake' and timeless relevance of the Qur'an in guiding human conduct across various life domains. Besides, this study contributes to scholars and educators interested in linguistic dimensions of religious discourse, as well as for preachers to build effective communication of their religious teachings in contemporary settings.